Ethnic status and engagement with health services: Attitudes toward help-seeking and intercultural willingness to interact among South East Asian students in Australia. (April 2017) - Logan, Shanna; Steel, Zachary; Hunt, Caroline
Previous research has demonstrated the importance of intercultural willingness to interact; however, these investigations have yet to be applied to a health context or to compare an ethnic minority with a majority sample. Consequently, the current study sought to better understand engagement with health services by investigating both attitudes towards seeking psychological help and intercultural willingness to interact within an ethnic minority South East Asian population, relative to an Anglo Australian sample. As predicted, negative attitudes towards seeking psychological help were higher in the South East Asian sample, with this relationship persisting across generations, despite significant differences in acculturation. In contrast, intercultural willingness to interact was not associated with ethnicity status but was associated with higher anxiety, uncertainty, ethnocentrism and help-seeking, consistent with current empirical and theoretical literature. The current study also sought to examine factors associated with help-seeking attitudes and found that ethnocentrism was a significant predictor, when accounting for previous health experience.